Poéticas espectatoriales en Hispanoamérica y Brasil (1800-1847) Ilustración - emancipación - convivencias excluyentes - Fernández, Hans (MIMESIS, 2022)
This book offers the first panoramic study on the development and characteristics of the literary-journalistic genre of spectator periodicals in Hispanic America and Brazil. After contextualizing these publications within the emancipation processes of 19th-century American Enlightenment, it explores the new coexistence modes and esthetics they disseminated.